The World Health Organization and the global standardization of medical training, a history - George Weisz; Beata Nannestad (BMC, 2021)
Abstract Background This article presents a history of efforts by the World Health Organization and its most important ally, the World Federation for Medical Education, to strengthen and standardize international medical education. This aspect of WHO activity has been largely ignored in recent historical and sociological work on that organization and on global health generally. Methods Historical textual analysis is applied to the digitalized archives and publications of the World Health Organization and the World Federation for Medical Education, as well as to publications in the periodic literature commenting on the standardization of international medical training and the problems associated with it. Results Efforts to reform medical training occurred during three distinct chronological periods: the 1950s and 1960s characterized by efforts to disseminate western scientific norms; the 1970s and 1980s dominated by efforts to align medical training with the WHO's Primary Healthcare Policy; and from the late 1980s to the present, the campaign to impose global standards and institutional accreditation on medical schools worldwide. A growing number of publications in the periodic literature comment on the standardization of international medical training and the problems associated with it, notably the difficulty of reconciling global standards with local needs and of demonstrating the effects of curricular change.